Preparation of Co/Cr-MOFs for efficient removal of fleroxacin and Rhodamine B - Wei Fuhua; Wang Yan; Ren Qinhui; Zhang Qin; Chen Hongliang; Liang Zhao (Green Processing and Synthesis)
Cr/Co-MOFs were synthesized via a solvothermal method using chromium acetate and cobalt chloride hexahydrate as metal ions, and trimeric acid as the organic ligand. The structures of Cr/Co-MOFs were characterized using Fourier infrared spectroscopy, X-ray diffraction, and scanning electron microscopy techniques. These Cr/Co-MOFs were used for removing organic contaminants in wastewater treatment. Fleroxacin and Rhodamine B (RhB) were specifically selected as target molecules in this study to evaluate the removal efficiency based on the mass of Co/Cr-MOFs, concentrations of organic contaminants, and adsorption time. Experimental findings indicated that at a Co/Cr-MOFs dosage of 100 mg, with initial concentrations of Fleroxacin (30 ppm) and RhB (20 ppm), removal efficiencies achieved were 95% and 99%, respectively. Within a timeframe of 5 h, Co/Cr-MOFs attained adsorption capacities amounting to 269.6 mg·g−1 for fleroxacin and 289.5 mg·g−1 for RhB. The interaction between Co/Cr-MOFs and fleroxacin, as well as RhB, is primarily attributed to factors such as pore size, hydrogen bonding, electrostatic charge, and π–π interactions. Moreover, theoretical analysis corroborated these experimental results by demonstrating conformity between the adsorption process and both second-order kinetic model equations alongside Langmuir isotherm model equations. Collectively, the experimental data combined with theoretical investigations underscore the practical significance associated with employing Co/Cr-MOFs for effective eradication of organic pollutants.